2016
DOI: 10.18869/acadpub.jafm.68.228.24135
|View full text |Cite
|
Sign up to set email alerts
|

Soret and Dufour Effects on MHD Mixed Convection Heat and Mass Transfer of a Stagnation Point Flow towards a Vertical Plate in a Porous Medium with Chemical Reaction, Radiation and Heat Generation

Abstract: The objective of this paper is to analyze the effects of heat and mass transfer in the presence of thermal radiation, internal heat generation and Dufour effect on an unsteady magneto-hydrodynamic mixed convection stagnation point flow towards a vertical plate embedded in a porous medium. The non-linear partial differential equations governing the flow are transformed into a set of ordinary differential equations using suitable similarity variables and then solved numerically using shooting method together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…analyze the effects of Dufour and Soret on MHD mixed convection flow with heat and mass transfer from a vertical flat plate embedded in a saturated porous medium taking into the influence thermophoresis, viscous dissipation, and radiation. Other relevant work to this paper could be found in Reference …”
Section: Introductionmentioning
confidence: 99%
“…analyze the effects of Dufour and Soret on MHD mixed convection flow with heat and mass transfer from a vertical flat plate embedded in a saturated porous medium taking into the influence thermophoresis, viscous dissipation, and radiation. Other relevant work to this paper could be found in Reference …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the concentration was increased by the enhancing Soret values. Karthikeyan et al [13] examined magneto-hydrodynamic mixed convection of a chemically reactive stagnation point stream towards a vertical plate in a medium with porosity which includes radiation and thermal generation under the influence of Soret and Dufour. Beg et al [14] considered the problem of natural convection MHD mass and energy transport from an extended surface in a saturated porous medium with Dufour and Soret impacts.…”
Section: Introductionmentioning
confidence: 99%
“…He found that the thermal boundary layer thickness increased with the rise of the heat generation or absorption parameter. The heat generation e ect on boundary layer ow with di erent uids has been investigated in some papers [16][17][18][19][20][21]. Hayat et al [22] analyzed convective ow of a second-grade liquid over a stretchy wall with convective surface condition.…”
Section: Introductionmentioning
confidence: 99%